2013
DOI: 10.1097/ijg.0b013e31824c9251
|View full text |Cite
|
Sign up to set email alerts
|

Features of Optic Disc Progression in Patients With Ocular Hypertension and Early Glaucoma

Abstract: Purpose To determine the clinical features of optic disc progression in patients with ocular hypertension and early glaucoma. Patients 336 eyes of 168 patients with ocular hypertension or early glaucoma Methods Two glaucoma specialists independently graded the baseline and most recent optic disc photographs for optic disc progression. Optic disc progression was defined as: new or increased neuroretinal rim thinning (two or more clock hours), notching (one clock hour or less of thinning of the neuroretinal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 34 publications
0
20
0
Order By: Relevance
“…Glaucoma characteristically has subtle optic disc changes in mild and moderate stages, with functional impairments only detectable in advanced disease. [26][27][28] The RAAB study conducted by Ramke et al 5 in 2012 reported the prevalence of glaucoma to be 2.9% in the blind and visually impaired groups. We found the prevalence to be much higher at 15.36%, which is in the context of a clinical cohort including all causes of glaucoma and improved sensitivity and specificity for detection.…”
Section: Discussionmentioning
confidence: 97%
“…Glaucoma characteristically has subtle optic disc changes in mild and moderate stages, with functional impairments only detectable in advanced disease. [26][27][28] The RAAB study conducted by Ramke et al 5 in 2012 reported the prevalence of glaucoma to be 2.9% in the blind and visually impaired groups. We found the prevalence to be much higher at 15.36%, which is in the context of a clinical cohort including all causes of glaucoma and improved sensitivity and specificity for detection.…”
Section: Discussionmentioning
confidence: 97%
“…Lloyd and colleagues 9 examined disc photographs in a group of 336 eyes of 168 patients with ocular hypertension or early glaucoma and found that 27.4% of eyes exhibited progression after a median of 6.1 years. Of the eyes with progression, excavation was seen in 89%, rim thinning in 54%, and notching in 16%.…”
Section: Optic Nerve Imagingmentioning
confidence: 99%
“…The most common location of change was in the inferotemporal quadrant of the disc, although 30% of cases exhibited progression in more than 1 location. 9 …”
Section: Optic Nerve Imagingmentioning
confidence: 99%
“…The most common location of change was in the inferotemporal quadrant of the disc, although 30% of cases exhibited progression in more than 1 location. 9 In assessing the optic nerve, Tatham et al 10 postulated a nonlinear relationship between retinal ganglion cell (RGC) estimate and cup-to-disc ratio. They concluded that cup-to-disc ratio is not sensitive for evaluating progressive neural losses in glaucoma, as small changes can be associated with large losses of RGCs.…”
Section: Optic Nerve Imagingmentioning
confidence: 99%